Determination of diffuser bubble size in computational fluid dynamics models to predict oxygen transfer in spiral roll aeration tanks. (August 2016) - Terashima, Mitsuharu; So, Magnus; Goel, Rajeev; Yasui, Hidenari
Abstract: The aeration tank is one of the most important processes in the biological wastewater treatment and water reuse system to remove organic pollutants in wastewater. The prediction of oxygen transfer using the computational fluid dynamics (CFD) method is crucial for minimizing the energy consumption of the aeration tank, which is one of the highest energy consuming units in a wastewater treatment system. Bubble size ( dB ), which is a critical parameter in the CFD simulations, was investigated for different types of diffusers. CFD calculations were conducted to simulate the hydraulics in different aeration tanks and the calculated values of the volumetric oxygen mass transfer coefficient ( KL a ) were compared with experimentally measured data. A total of 19 tanks containing clean water and 8 tanks containing wastewater with different diffuser types and aeration intensities were simulated. The KL a values determined for these configurations were fitted using a calibrated dB value specified in the CFD simulations. The results of the calculations indicate that the coarse-bubble diffusers, fine-pore diffusers, and slitted membrane diffusers have bubble sizes of 7–8 mm, 5–6 mm, and approximately 3 mm, respectively. Additionally, CFD simulations were conducted to simulate the flow pattern and calculate the corresponding KL a value when the diffuser configuration was changed.